Do institutions matter? Explaining the use of working time flexibility arrangements of companies across 21 European countries using a multilevel model focusing on country level determinants - Heejung Chung (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
This paper explores the reasons behind the differences in the use and provision of different types of working time flexibility options of companies across European labour markets with a special focus on the country differences. Competing theories on the cross-country variances of labour market flexibility are tested to examine whether labour market institutions are the driving forces of working time flexibility practices in comparison to other factors such as economic, labour market structures and cycles. It uses a multi-level model which enables examination of companies in the context of the country in which it is embedded, while including both company and country level characteristics in the explanatory model. In this paper, the issue of flexibility is addressed broadly, thus, it perceives labour market flexibility as a method used for the needs of employees as well as for those of employers. In addition, the 'flexible firm' approach is taken and various flexibility options are considered to be bundles of arrangements with similar latent characteristics and not as separate entities. Based on this, the paper explains the differences between countries where there are more worker-oriented working time flexibility options to those where flexibility practices are more companyoriented. – – In der vorliegenden Analyse werden die Hintergründe für den unterschiedlichen Einsatz verschiedener Modelle zur flexiblen Arbeitszeitgestaltung von Unternehmen in europäischen Arbeitsmärkten untersucht. Das besondere Interesse liegt auf den Unterschieden zwischen den einzelnen Ländern. Dabei werden konkurrierende Theorien über Varianzen der Arbeitsmarktflexibilität zwischen den Ländern getestet um zu untersuchen, ob institutionelle Arbeitsmarktregelungen die treibenden Kräfte für unterschiedliche Anwendungen flexibler Arbeitszeiten sind verglichen mit anderen Einflussfaktoren wie bspw. Arbeitsmarktstrukturen und Konjunkturzyklen. Hierzu wird ein Mehr-Ebenen-Modell geschätzt, welches die Betrachtung eines Unternehmens in dessen jeweiligem Landeskontext ermöglicht; dazu werden Unternehmensund Ländercharakteristika als erklärende Variablen herangezogen.
Keywords: 330